2010
DOI: 10.1186/1471-2458-10-775
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with organic food consumption during pregnancy; data from a large cohort of pregnant women in Norway

Abstract: BackgroundLittle is known about the use of organic food during pregnancy. The aim of this study was to describe characteristics associated with the use of organic food among pregnant women participating in the Norwegian Mother and Child Cohort Study (MoBa).MethodsThe present study includes 63,561 women who during the years 2002-2007 answered two questionnaires, a general health questionnaire at gestational week 15 and a food frequency questionnaire at weeks 17-22. We used linear binomial regression with freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
35
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 45 publications
10
35
1
1
Order By: Relevance
“…Consistent with previous studies (25,45,(47)(48)(49) , we found herein that income seemed to be a weak determinant compared with education to explain differences in organic food consumption behaviours. However, whether high consumption of organic foods was not necessarily related to high household income, low consumers exhibited elevated percentages of individuals with a low income in accordance with another work (49) .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies (25,45,(47)(48)(49) , we found herein that income seemed to be a weak determinant compared with education to explain differences in organic food consumption behaviours. However, whether high consumption of organic foods was not necessarily related to high household income, low consumers exhibited elevated percentages of individuals with a low income in accordance with another work (49) .…”
Section: Discussionsupporting
confidence: 91%
“…However, this pattern does not necessarily apply when organic food consumption is related to an alternative lifestyle that www.annualreviews.org • Exposure and Health Implicationsincludes vegetarianism, environmentalism, or other ideologies (10,48,89,107). Studies show that frequent organic consumption does not follow a typical age gradient but is found in both young adult (<25 years) and older adult (>40 years) age groups (81,107) and that organic consumers more often belong to households with children than do nonorganic consumers (48).…”
Section: Characteristics Of Organic Consumersmentioning
confidence: 99%
“…A study in a large population of pregnant women in Norway showed that frequent organic consumers more often participated in regular exercise and had lower BMI, characteristics associated with a healthy lifestyle. However, frequent organic consumption was also associated with higher prevalence of smoking and use of alcohol, characteristics that are not typical of a health-conscious lifestyle (107).…”
Section: Characteristics Of Organic Consumersmentioning
confidence: 99%
See 2 more Smart Citations